Human enhancement and morality: some theoretical doubts - Cekić, Nenad (Sociološki pregled, 2024)
The author tackles the critical ethical ideas accompanying the idea that man can be “morally enhanced” by influencing the “moral brain”. Analyzing the primary approach of contemporary neuroethicists, the author notes that the idea of improvement mainly omits normative-ethical and metaethical elements, without which a clear idea of what can be considered “moral enhancement” is not possible. The author also draws attention to the over-reliance on technological procedures in assessing the determination and scope of moral enhancement. At the end of the paper, the author analyzes two models of the functioning of the “moral brain”. These two models are taken from pop culture. One is the model of the dual personality of Dr. Jekyll / Mr. Hyde, taken from literature and film adaptations. The second is the famous computer with personality, HAL 9000 from the renowned movie 2001: A Space Odyssey.
Keywords: ethics; neuroethics; moral enhancement; moral brain; models